ELECTROCHEMICAL STUDIES OF TETRACROWN-ETHER SUBSTITUTED PHTHALOCYANINES IN SOLUTION - ÖZKAYA, ALİ RIZA (GORDON BREACH SCI PUBL LTD, 1994)
Cyclic voltammetry of soluble metal-free and copper phthalocyanines with crown ethers attached to the periphery through oxymethyl bridges show two one-electron reduction processes on sweeping to negative potentials. The addition of sodium or potassium ions to the solution results in a decrease in diffusion coefficients, which is a consequence of intermolecular complex formation in the presence of these two cations.
Keywords: PHTHALOCYANINES; COPPER; CROWN ETHER; ELECTROCHEMISTRY; METAL PHTHALOCYANINES; COPPER PHTHALOCYANINE; CROWN ETHERS; MOIETIES; WATER; VOLTAMMETRY